Human hair follicle and interfollicular keratinocyte reactivity to mouse HPV16-transformed cells: an in vitro study - Smetana, Karel; Dvoránková, Barbora; Lacina, Lukás; Cada, Zdenek; Vonka, Vladimír (Oncology reports, 2008)
The role of stem cells in cancer formation and spreading has been established. As with normal tissue, the cancer stem cells need a special microenvironment to support their growth. This microenvironment may be represented by the tumor stroma. One of the possible ways of tumor stromal formation is the epithelial-mesenchymal transition of tumor epithelium. Following this mechanism, stromal cells must share the basic genetic alterations with the tumor cells. In an attempt to create a system capable of testing some aspects of the mesenchymal cell-keratinocyte interactions, we studied the effects of the fibroblastoid mouse TC-1 cells that were prepared by the introduction of human papillomavirus type 16 (HPV16) genes E6 and E7 to lung epithelial cells on the phenotype of normal human interfollicular and hair follicle keratinocytes. From this point of view, they may resemble stromal cells formed by the epithelial-mesenchymal transition of cells from HPV-induced squamous cell carcinoma. In contrast to 3T3 murine embryonic fibroblasts which were used as control cells, TC-1 cells influenced not only the size of the keratinocytes and the shape of their colonies, but also induced the expression of keratins 8 and 19 and vimentin. In conclusion, TC-1 cells exhibited a marked biological activity by influencing the behavior of the normal human follicular and intefollicular keratinocytes. This observation is compatible with the hypothesis that stromal cells play an important role in tumor progression and spreading.
Keywords: Fibroblasts; Human papillomavirus 16; buňky 3T3; keratin-8; Humans; Keratinocytes; keratinocyty; Phenotype; lidé; zvířata; myši; Stromal Cells; buňky stromatu; nádorová transformace buněk; myši inbrední C57BL; Vimentin; Mice; Hair Follicle; Cell Size; 3T3 Cells; fenotyp; Mice, Inbred C57BL; Neoplasms; Keratin-8; Cell Transformation, Neoplastic; nádory; fibroblasty; vlasový folikul; Animals; velikost buňky; lidský papilomavirus 16; vimentin